Rapid Colorimetric Sensor Based on Gold Nanoparticles Functionalized 4-Amino-3-hydrazino-5-mercapto-1,2,4-triazole for Cortisol Detection in Saliva Sample - Ni Nyoman Tri Puspaningsih; Ganden Supriyanto; Nasronudin Nasronudin; Hanim Istatik Badi'ah (Universitas Gadjah Mada, 2023)
The rapid, simple, and selective colorimetric sensing method of cortisol has been successfully developed using AuNPs modified with 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole (AuNPs-AHMT). The principle of this method is based on the color change from wine red to purple (redshift) when AuNPs-AHMT interacts with cortisol. The hydrogen bonding between the hydroxyl group from cortisol and the amine group from AHMT induces the aggregation of AuNPs. The modification of the AuNPs surface with AHMT aims to increase its stability. The properties of AuNPs and AuNPs-AHMT were characterized by UV-vis spectrophotometer. The interaction between AuNPs-AHMT and cortisol was studied by UV-vis and FTIR spectroscopies. The proposed method was optimized and validated. Au(III) was reduced to AuNPs at an optimum NaBH4 concentration of 1.0 mM. Validation of the proposed method showed good analytical performance with linearity from 1.0–50.0 nM, accuracy 91.07–102.77%, intra-day precision < 2.22% and inter-day precision < 2.17%, detection limit 0.76 nM, quantification limit 2.54 nM, and sensitivity 0.0112 nM/mL. The proposed method also showed good selectivity with the presence of some interferences in the sample. The proposed method was successfully applied for the determination of cortisol in the saliva by the standard addition method with acceptable recovery.